Takotsubo syndrome in a premenopausal patient. (17th February 2018) - Menezes, Maria; Marto, Daniela; Marcão, Isabel; Salvado, Catarina
Abstract : Takotsubo syndrome is a rare clinical condition, with a pathophysiology that is not fully understood. Characterised by an acute and usually reversible heart failure, the condition is often preceded by a stressful event. For the diagnosis of Takotsubo syndrome to be possible, the absence of coronary artery disease as a cause is required. We report a case of Takotsubo syndrome in a 47-year-old woman of fertile age. Electrical and echocardiographic presentations were classical in the patient. However, abnormally elevated cardiac biomarkers were registered. The patient showed signs of clinical improvement, with a follow-up angiography excluding coronary artery disease and therefore leading to a diagnosis of Takotsubo syndrome.